Determination of lithium and transition metals in Li1Ni1/3Co1/3Mn1/3O2 (NCM) cathode material for lithium‐ion batteries by capillary electrophoresis. Issue 3 (14th December 2016) - Vortmann‐Westhoven, Britta; Lürenbaum, Constantin; Winter, Martin; Nowak, Sascha
Abstract : In this work, we present a novel electrophoretic method that was developed for the determination of lithium and transition metals in LiNi1/3 Co1/3 Mn1/3 O2 cathode material after microwave digestion. The cations in the digested LiNi1/3 Co1/3 Mn1/3 O2 material were separated by CE and the element content was determined by UV/Vis detection. To characterize the precision of the measurements, the RSDs and concentrations were calculated and compared to those obtained with ICP‐optical emission spectrometry (ICP‐OES). Furthermore, a certified reference material (BCR 176R —fly ash) was investigated for all techniques. For active material components, the LOD and LOQ were determined. The LODs and LOQs for the metals determined by CE were as follows: lithium (LOD/LOQ): 17.41/62.70 μg/L, cobalt (LOD/LOQ): 348.4/1283 μg/L, manganese (LOD/LOQ): 540.2/2095 μg/L, and nickel (LOD/LOQ): 838.0/2982 μg/L. Recovery rates for lithium were in the range of 95–103%. It could be proven that with the new technique, the results for the determination of the lithium content of active material were comparable with those obtained by ICP‐OES and ion chromatography. Furthermore, the recovery rates of the transition metals were determined to be between 96 and 110% by CE and ICP‐OES.